Advances in antithrombotic therapy as adjunct to reperfusion therapies for ST-segment elevation myocardial infarction - De Luca, Giuseppe; Marino, Paolo (Thrombosis and Haemostasis, 2008)
The treatment of ST-segment elevation myocardial infarction (STEMI) has improved over the past decades, mainly due to reperfusion therapies. The aim of this article is to provide an updated review of adjunctive antithrombotic therapy to reperfusion strategies for STEMI. As compared to unfractionated heparin (UFH), among patients treated with thrombolysis, low-molecular- weight heparins (LMWHs),mainly enoxaparin, fonda-parinux and clopidogrel have been shown to improve outcome in terms of death and reinfarction, whereas GP IIb-IIIa inhibitors, mainly abciximab, and direct thrombin inhibitors have reduced reinfarction, but not mortality. Among patients undergoing primary angioplasty, early UFH should still be regarded as the gold standard in anticoagulation therapy. In addition to ASA, early GP IIb-IIIa inhibitors, especially abciximab, should be considered since it has been shown to provide further benefits in terms of preprocedural recanalization. Despite the positive results observed in the HORIZONS trial, additional studies are needed to investigate the role of bivalirudin as compared to abciximab administration. In our opinion, bivalirudin may be considered instead of GP IIb-IIIa inhibitors among STEMI patients at high risk for bleeding complications. Due to the very low mortality currently achieved by primary angioplasty, a further reduction in short- or medium-term mortality would be quite improbable to be observed. Thus, additional endpoints, such as infarct size and myocardial perfusion, may be considered in future randomized trials among patients undergoing mechanical revascularization for STEMI.
Keywords: Acute myocardial infarction; direct antithrombin agents; atherothrombosis; antiplatelet drugs; heparins / LMWH